Autoconsciência desejante na Fenomenologia do Espírito: negatividade metafísica e liberdade (Revista Eletrônica Estudos Hegelianos, 2022)
The aim of this article is to show how the concept of desire elucidates the metaphysical negativity present in Hegel’s Phenomenology of Spirit (1807), as well as to explain the true meaning of the independence of self-consciousness from reality. The guiding line is the presentation of the experience of consciousness with a focus on the transition from dualistic metaphysics, defended by the understanding, to the metaphysics of selfconsciousness. Self-consciousness seizes negativity as life that animates reality and, principally, as desire, seizes negativity as the movement of reconfiguration of the relationship between subject and object, between identity and difference. Therefore, by reading Judith Butler in Subjects of Desire (1987), the text aims to make explicit how the reflexivity inherent in the self-positioning of the subject as a pure self, puts the conditions of the manifestation of self-consciousness as desire.